Numerical investigation on the combined effects of varying piston bowl geometries and ramp injection rate-shapes on the combustion characteristics of a kerosene-diesel fueled direct injection compression ignition engine. (15th March 2017) - Tay, Kun Lin; Yang, Wenming; Zhao, Feiyang; Yu, Wenbin; Mohan, Balaji
Highlights: Effect of injection rate-shaping on heat-release is significant with less turbulence. Two peak heat-releases are seen for the shallow-depth re-entrant piston. Significant combustion phasing occurs with kerosene usage and high turbulence. Abstract: In this work, the combustion characteristics of a direct injection compression ignition (DICI) engine fueled with kerosene-diesel blends, using different piston bowl geometries together with varying injection rate-shapes were investigated. A total of three combustion bowl geometries, namely the omega combustion chamber (OCC), the shallow-depth combustion chamber (SCC) and the shallow-depth re-entrant combustion chamber (SRCC), were used together with six different ramp injection rate-shapes and pure diesel, kerosene-diesel and pure kerosene fuels. It is seen that the SRCC geometry, which has the shortest throat length, gives the highest turbulence kinetic energy (TKE) and this resulted in two peak heat-releases, with a primary peak heat-release during the premixed combustion phase and a secondary peak heat-release during the mixing-controlled combustion phase. In addition, the SCC geometry gives rather distinct premixed combustion and mixing-controlled combustion phases due to the fact that combustion is predominantly controlled by the injected fuel spray itself because of less turbulence. Also, when kerosene is used in place of diesel, the heat-release during the premixed combustion phase increases and diminishes during the mixing-controlled and late combustion phases. It is interesting to note that the effect of injection rate-shaping on the heat-release rate is more obvious for bowl geometries that generate less TKE. Moreover, bowl geometries that generate higher TKEs as well as fuels with lower viscosities generally give lower carbon monoxide (CO) emissions and higher nitrogen oxide (NO) emissions. More importantly, it is possible to achieve low NO and CO emissions simultaneously by using the appropriate bowl geometry, injection rate-shape and fuel, although a slight decrease in power is inevitable.